Teaching Critical Thinking in English Subject - Guo Simin; Intan Safinas Mohd Ariff Albakri (International Journal of Education, Information Technology, and Others, 2022)
Critical Thinking (CT) has been recognized as one of the most significant thinking skills and indicators of students’ learning quality. Enterprises need talents who can think critically to solve problems. Countries need to cultivate generations with independent personality and thinking capability to think out of the box. It has been proven by numbers of researchers that CT can be taught in class. To develop successful critical thinkers, CT must be incorporated into curriculum content and teaching approaches and sequenced at all grade levels. This research provides a review of the literature on teaching CT skills in English subject. The review discussed the importance of thinking skills, the integration of CT in language class, present studies on CT in English reading class and the need to train teachers to master CT skills. The results indicate teaching CT skills is of great value for English learners. The design of curriculum and training of teachers are crucial for learners’ thinking skill development.